Contagion on financial markets - Konečný, Vojtěch; Křečková Kroupová, Zuzana, 1972-; Taušer, Josef; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2017)
This thesis investigated cases of how and if financial contagion spread from stock markets of the Southern Europe, to the two regions of the 2004 enlargement of European Union; the Baltics states and the Central European (CEE) countries (and their stock markets). We defined two research questions that we wanted to answer. First, if having a single currency increases cross-country co-movements between two countries (stock markets) that are using the same currency. Comparing the volume of co-exceedances between both regions, we can say that the single currency does not have effect on the volume of contagion moments. We can clearly see that the region of Central Europe experienced higher volume of both positive and negative extreme returns transmitted from the Southern Europe, than was the case of Baltic region, whose countries has been in the ERM mechanism since 2005.
Vedoucí práce: Zuzana Křečková Kroupová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: economics of globalisation and european integration [obor dipl. práce]; diplomové práce; master's theses